Raḍā’ Era Nabi Muhammad dan Modern: Analisis Korelasi, Resepsi Muslim Jawa Timur, dan Solusi - Amran Amran (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Raḍā' in the Era of the Prophet Muhammad and the Modern: Correlation Analysis, East Java Muslim Reception, and SolutionsRaḍā' is a tradition that existed at the time of the Prophet Muhammad. History records that the Prophet breastfed Aminah for no more than 10 days. Then the Prophet was breastfed by another woman. Raḍā' at the time of the Prophet was carried out directly, namely the baby's mother entrusted her baby to another woman. Over time, the concept of Raḍā' changed with the existence of an institution that operated as a reservoir for breast milk from breast milk donors. Then distribute it to the baby's mother in need. This change in concept raises its own problems because with the existence of breastfeeding donor institutions, breastfeeding is prone to occur. Whereas the existence of a breastfeeding donor agency is a breakthrough for babies in need. This article is here to find a correlation between breastfeeding at the time of the Prophet Muhammad and modern breastfeeding donor agencies. Furthermore, this article looks for solutions to prevent the existence of milk marriages that are feared by Muslims. This article uses mixed methods research as a step to find the results. The results obtained from this article show a strong correlation between Rada' at the time of the Prophet and the modern Rada' system. To avoid the existence of incestuous marriages, the researcher proposes the existence of administrative records, thus preventing the existence of breast marriages in Indonesia.